Detection of ketamine in human plasma by High Performance Liquid Chromatography (HPLC) and Thin Layer Chromatography (TLC)- A Preliminary Study - Ali, Siti Zafira Mat (Universiti Sains Malaysia, 2016)
Ketamine was one of the new psychoactive substance (NPS) which is increasingly abused nowadays. The aim of this study was to detect the ketamine in human plasma by two different chromatographic methods of high performance liquid chromatography (HPLC) and thin layer chromatography (TLC). Liquid-liquid extraction (LLE) for ketamine in human plasma was used for both methods. In HPLC analysis of ketamine, the stationary phase for HPLC separation of ketamine and internal standard, morphine in human plasma was C18 column (150 X 4.6 mm I. D, particle size 2.7 pm) and the mobile phase consist of 23% acetonitrile and 77% phosphate buffer with pH 7.2. The HPLC system was equipped with photodiode array (PDA) detector. The optimization of chromatographic conditions was done by varying the flow rate of mobile phase and different concentration of drug standard. Flow rate 1.0 ml/min was chosen and the lowest concentration of ketamine that can be detected by the HPLC Waters 2695 Separation Module was 5 pg/ml. The optimization of extraction was done by varying the types of solvents used for extraction of drug from plasma. The percentage recoveries obtained for the solvents used in this study was more than 100%. In TLC analysis of ketamine in human plasma, the stationary phase was HPTLC Silica gel 60 F254. The analysis was done by varying the liquid-liquid extraction methods and varying the mobile phase. The good separation of ketamine was achieved using acid-back liquid extraction method and mobile phase consist of ethyl acetate: methanol: concentrated ammonia solution 28% (8.5:1:0.5). The Rf value calculated was 0.92 and the lowest concentration for ketamine in plasma that can be detected was 10 pg/ml. Ketamine was detectable with TLC and HPLC methods. The optimization of liquidliquid extraction for HPLC analysis was required in future studies.